(untitled) (Acta Scientiarum. Agronomy, 2018)
Spraying practices are highly sensitive to variations in climatic conditions, so it the spatial variability of the number of monthly hours available for the application of pesticides in the state of Paraná, Brazil, was determined and analyzed. An hourly time series of the climatic data obtained from 54 meteorological stations from the Paraná, for the years 2004-2014 was analyzed. To determine the number of monthly hours available to perform the applications, the following conditions were established: temperature < 30°C, relative air humidity > 55%, wind speed between 3 and 12 km h-1, and rainfall less than 0.2 mm h-1. After being cross-referenced, these data were analyzed using descriptive statistics and geostatistics. A high variability of availability for the performance of the applications was found, with 46.59 hours in June and 285 hours in August. A spatial dependence existed in the time available to perform pesticide applications in the state of Paraná, with variation occurring as a function of the month of the year. The Paraná geographic regions of the Central East, Metropolitan Curitiba, and Southwest are less favorable to perform the application. The mapping allows the management of spraying practices.